Rancang Bangun Alat Metal Detector dengan Metode Beat Frequency Oscillator - Suhaesih Rianto; Syahrir Syahrir; Adrianus Inu Natalisanto (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2022)
A metal detector using the Beat Frequency Oscillator principle and solenoid induction has been made using a series of tools (IC NE 555, capacitors with values ​​of 3.3 F and 4.7 F, resistors 4.9 kΩ, enamel wire 0.3 mm, 4Ω 3W speakers, and 9V battery). The measuring limit of the tool is obtained through measurements using a metal material, namely iron, where the measured value variables are the value of frequency and voltage Vpp, and the average value of the frequency in the input data after the object is 868.1786 Hz and the average value of the Vpp voltage is 1,427 Volts. While the output data obtained the average frequency value is 863.4895 Hz and the average value of Vpp voltage is 0.325 Volt after the object, as for the sound produced before and after the object the difference is too small, so an amplifier circuit is added using an IC LM386 as Audio Amplifier.